Analiza kampanii wyborczej oraz wyników wyborów czerwcowych z 1989 roku z uwzględnieniem ich percepcji przez dzisiejszą młodzież - Mielewczyk, Margaretta (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The elections of June 1989 is considered as the symbol of Polish political transformation. It was the first partially independent elections after the period of Polish People’s Republic. It was characterized by the possibility of participation of the opposition and by the real competitiveness to which the coalition-governmental party of that time was not used to. Therefore, the party had no experience in conducting a competitive campaign. Despite the agreement during the Round Table meeting and agreed distribution of seats, the Solidarity [‘Solidarność’] group gained a resounding victory expressed in the high public support and winning almost all seats contested in the first round of elections. The objective of this article is to analyze the course of the campaign and the results of the elections of June 1989.